Association between Dietary Patterns and Chronic Diseases among Chinese Adults in Baoji. (21st September 2014) - Wang, Honglin; Deng, Feng; Qu, Meng; Yang, Peirong; Yang, Biao
Abstract : Objective . This study was aimed to identify the dietary patterns among Chinese adults in Baoji and explore the association between these dietary patterns and chronic diseases. Methods . With multistage stratified random sampling and semiquantitative food frequency questionnaire, the prevalence of chronic disease and dietary intake was investigated in 2013. We used factor analysis to establish dietary patterns. Results . A total of 5020 participants over 15 years old were included in this study. Five dietary patterns were identified in Baoji named as protein, balanced, beans, prudent, and traditional patterns. There are many protective effects with protein, balanced, and beans dietary patterns on chronic diseases. Conclusions . We should encourage Baoji city residents to choose protein, balanced, and beans dietary patterns and abandon prudent and traditional patterns.